Conservation Agriculture 2014
DOI: 10.1007/978-3-319-11620-4_6
|View full text |Cite
|
Sign up to set email alerts
|

Insect Pest Management in Conservation Agriculture

Abstract: Insects are a dominant form of life on Earth with more than 1 million described species. Yet, only 1% competes with humans for food, shelter, and space. Various farming systems have been adopted for sustainable pest management but none have been entirely successful in managing insect pests. Chemical insecticides are still the predominant pest control measure but cause health hazard and environmental pollution. The long-term sustainability of agricultural and natural ecosystems depends upon the conservation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…Xiong [33] found highest peaks during 4 th week of February. Nawaz [34] found highest peaks at milking stage during 3 rd week of March. Rustamani et al [26] found highest peaks at heading or earing stage.…”
Section: Resultsmentioning
confidence: 94%
“…Xiong [33] found highest peaks during 4 th week of February. Nawaz [34] found highest peaks at milking stage during 3 rd week of March. Rustamani et al [26] found highest peaks at heading or earing stage.…”
Section: Resultsmentioning
confidence: 94%
“…According to van Evert, Gaitán-Cremaschi, Fountas and Kempenaar (2017), a site-specific management in olive orchards is leading to an increase in productivity and product quality. In addition, Nawaz and Ahmad (2015) and Choudhary et al…”
Section: (360) 2019mentioning
confidence: 98%
“…Yet, organic and conservation agricultures share common principles, like enhancing biological activity to increase resilience and autonomy. As conservation agriculture does not specifically address pest management, it could benefit from strategies and knowledge developed in organic agriculture on pest and predator life cycles and their interactions with the environment to manage these without synthetic nor mechanical inputs (Nawaz and Jam Nazeer, 2015). Since no curative tools remain to control pests under OC farming strategy, a greater understanding of ecological functions underpinning this ecosystem service is required.…”
Section: Figurementioning
confidence: 99%